SIFAT-SIFAT SEASONING ALAMI JAMUR MERANG (Volvariella volvaceae) TERFERMENTASI MENGGUNAKAN TAPIOKA TEROKSIDASI SEBAGAI BAHAN PENGISI - Yhulia Praptiningsih; Niken Widya Palupi; Triana Lindriati; Inna Manikam Wahyudi (Faculty of Agricultural Technology, University of Jember, 2017)
The paddy straw mushroom can be make natural seasoning, because it has content of protein 17.01 % (db) which completely of amino acids composition,high content of glutamic acid and aspartic acid. Producing of natural seasoning from paddy straw mushrooms which has along life storage, practice and flexible, it is need of salted fermentation to hydrolyze of mushrooms protein. The aim of this research was to reach of the appropriate proportion of salted fermented paddy straw mushrooms and oxidized tapioca as a filler to produce the good properties and high preference of fermented paddy straw mushrooms seasoning. The yield of this research showed that the good treatment was the proportion of salted fermented paddy straw mushrooms and oxidized tapioca 75:25. The seasoning had the moisture content 14.1 %, total protein 17.98% (db), soluble protein 4.51 % (db), brightness 61.55, solubility 8.22 seconds, the preference score of colour 3.28 (rather like until like), aroma 2.92 (little like until rather like), taste 3.06 (little like until rather like), and overall 3 (rather like). Keywords: natural seasoning, fermented paddy straw mushrooms, oxidized tapioca, filler